Prevalence and genetic characteristics of Blastocystis hominis and Cystoisospora belli in HIV/AIDS patients in Guangxi Zhuang Autonomous Region, China - Ning Xu (Nature Portfolio, 2021)
Abstract Blastocystis hominis and Cystoisospora belli are considered to be common opportunistic intestinal protozoa in HIV/AIDS patients. In order to investigate the prevalence and genetic characteristics of B. hominis and C. belli in HIV/AIDS patients, a total of 285 faecal samples were individually collected from HIV/AIDS patients in Guangxi, China. B. hominis and C. belli were investigated by amplifying the barcode region of the SSU rRNA gene and the internal transcribed spacer 1 (ITS-1) region of the rRNA gene, respectively. Chi-square test or Fisher’s exact test were conducted to assess the risk factors related to B. hominis and C. belli infection. The prevalence of B. hominis and C. belli was 6.0% (17/285) and 1.1% (3/285) respectively. Four genotypes of B. hominis were detected, with ST3 (n = 8) and ST1 (n = 6) being predominant, followed by ST6 (n = 2) and ST7 (n = 1). Females had a statistically higher prevalence of B. hominis (11.6%) than males (4.2%). The statistical analysis also showed that the prevalence of B. hominis was significantly associated with age group and educational level. Our study provides convincing evidence for the genetic diversity of B. hominis, which indicates its potential zoonotic transmission and is the first report on the molecular characteristics of C. belli in HIV/AIDS patients in China.